Microbubbles Ultrasonic Cavitation Regulates Tumor Interstitial Fluid Pressure and Enhances Sonodynamic Therapy - Xi, Fen; Feng, Yuyi; Chen, Qiaoli; Chen, Liping; Liu, Jianhua (Frontiers in Oncology, 2022)
Sonodynamic therapy (SDT) is a promising treatment method for solid tumors. However, the high interstitial fluid pressure (IFP) in tumor tissues limits the accumulation of ultrasound-sensitive agents. In the present study, microbubble ultrasonic cavitation was used to regulate the tumor’s IFP and evaluate SDT effects. Rabbit VX2 tumor tissues were treated with microbubble ultrasonic cavitation. The IFP of different tumor parts before and after cavitation was measured by the WIN method. The accumulation of the ultrasound-sensitive agent hematoporphyrin monomethyl ether (HMME) in tumor tissues was observed using an ultramicro spectrophotometer and laser confocal microscope. Then, tumor-bearing rabbits were treated with SDT once a week for eight weeks and the therapeutic effect was evaluated. After microbubble ultrasound cavitation treatment, the tumor’s IFP decreased and the HMME concentration increased. We concluded that Microbubble ultrasound cavitation can increase HMME accumulation in rabbit VX2 tumors and increase SDT therapeutic effects.